Energy routing algorithm based on OSPF protocol and virtual circuit switching mode in energy local area network. (28th February 2020) - Ali, Babar; Murtaza, Ghulam; Mahmood, Tariq; Bilal, Hafiz Muhammad; Zahoor, Rizwan; Memon, Saleemullah
The advance management of the power supply to load such as in homes, offices, etc. and power from the source to central network in a smart grid system with lowest possible loss is considered here in this paper using the concept of energy internet. It also includes the complete details of power flow and control. In this paper, the efficiency of transmission is increased by using energy routers based on open shortest path first (OSPF) protocol, a new concept in the field of energy internet. By using energy local area network (e-LAN) concept, all the energy routers are connected by using OSPF protocols and virtual circuit concept theory. An algorithm is proposed for efficient power transmission and effective selection of sources to minimise the overall cost in the network.